AB0724 Glucose metabolism disturbances in never treated inflammatory arthritis patients. (23rd January 2014) - Ursini, F.; Grembiale, A.; Gagliardi, D.; Savarino, F.; Calabria, M.; Naty, S.; Grembiale, R. D.
Abstract : Background: Epidemiological studies show that inflammatory arthritis are characterized by an increased cardiovascular disease (CVD) risk [1 ]. This could be at least in part attributed to a high prevalence of insulin resistance and type 2 diabetes mellitus, as described in several rheumatic populations. Corticosteroid treatment contribute to the development of glucose metabolism disturbances in arthritis patients, thus making difficult to understand the role of the disease itself in the development of these conditions. Objectives: Aim of our work was to evaluate the prevalence of glucose metabolism disturbances (impaired fasting glucose, impaired glucose tolerance, combined IFG/IGT, type 2 diabetes mellitus) in never treated inflammatory arthritis patients. Methods: The study population consisted of subjects from the Rheumatology outpatient clinic of the Internal Medicine Unit, University of Catanzaro "Magna Graecia". For the present study 150 consecutive patients were evaluated and 52 fulfilled the inclusion criteria (16M/36F). We included patients who satisfied classification criteria for rheumatoid arthritis (ACR/EULAR criteria), psoriatic arthritis (CASPAR criteria), ankylosing spondylitis (modified New York criteria) or undifferentiated spondiloarthritis (ESSG criteria). Exclusion criteria were current or previous treatment with DMARD's or corticosteroids or other drugs known to influence glucose metabolism (such as metformin, sulfonylureas, thiazolidinediones, acarbose, dipeptidyl peptidase-4 inhibitors, and glinides, subcutaneous insulin, and thyroid hormones). Each patient underwent a standard 75-mg oral glucose tolerance test after overnight fasting. We defined impaired fasting glucose (IFG, fasting glucose between 100 and 125 mg/dL), impaired glucose tolerance (IGT, 2 hr glucose value in the OGTT between 140 and 199 mg/dL), and type 2 diabetes (T2DM, fasting glucose level ≥ 126 mg/dL in two occasions, or glucose ≥ 200 mg/dL at the 2nd hr of the OGTT) using ADA criteria [2 ] Results: Mean age was 54.6 ± 10.7. Among patients, 19 RA, 15 PsA, 3 AS, 15 uSpA. We found an overall prevalence of glucose metabolism disturbances of 57, 7%. Diabetes Mellitus type 2 (DM2) was present in 10 patients, impaired fasting glucose (IFG) in 9 patients, impaired glucose tolerance (IGT) in 6 patients while combined IFG/IGT was present in 5 patients (table 1). Conclusions: In this study we have reported preliminary data suggesting an elevated prevalence of glucose metabolism disturbances in never treated inflammatory arthritis patients. Abnormal glucose metabolism is a common comorbidity in inflammatory arthritis, with a possible role in the development of atherosclerosis. According to our data glucose metabolism disturbances are elevated independently of corticosteroids use. References: Mok, C.C., et al., Prevalence of atherosclerotic risk factors and the metabolic syndrome in patients with chronic inflammatory arthritis. Arthritis Care Res (Hoboken), 2011. 63(2): p. 195-202. Standards of medical care in diabetes--2012. Diabetes Care, 2012. 35 Suppl 1: p. S11-63. Disclosure of Interest: None Declared